Effects of alkali metal ions on the formation of mesoporous alumina - Sun, Z; Zheng, T; Bo, Q; Vaughan, D; Warren, M (2008)
Mesoporous alumina (MA) samples with high surface area and comparatively narrow pore size distributions were synthesized for the first time using aluminium powder as an aluminium source and polyethylene glycol (PEG) as a structure directing agent via a sol-gel method in alkaline solution. Thermogravimetric and differential thermal analysis (TG/DTA), powder X-ray diffraction, small angle X-ray diffraction, transmission electron microscopy and nitrogen adsorption/desorption techniques were used to characterize the MA samples. The results indicate that the alkali metal ions used in the preparation play a significant role in determining the crystalline structure and morphology of the synthesized MA. In comparison with using aluminium chloride, γ-Al2O3 forms more readily using aluminium powder. © The Royal Society of Chemistry 2008.